Jungle GPS tracker and data logger system / Nabilah Zulkfali … [et al.] - Zulkfali, Nabilah; Ghazali, Mohd Zaki; Mohamed Noor, Noorhayati; Zainol, Zarina; Md Saidi, Raihana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Jungle trekker can easily get lost in Malaysian rainforest known for its thick jungle and everything looks the same. Often, helicopter fails to allocate this lost victim as the tree canopies blocks the trekker. The scorching heat and depleting food supplies leaving trekkers may not survive for long without immediate help. In this situation, the Jungle GPS Tracker and Data Logger System will be a lifesaver to a lost trekker. The Jungle GPS Tracker and Data Logger System consist of GPS receiver, transceiver and data logger. The GPS receiver passively receive satellite signal capable of sending the location to the GPS transceiver within 100m radius. The search and rescue team, who will be carrying the GPS transceiver, will receive the position of the tracker. The transceiver is equipped with a data logger, which will log the location with a timestamp to a USB flash drive. This information is useful for rescue team to allocate the victim who is already disoriented and weak. This system is useful for the jungle trekkers and forest ranger who understand the ordeal of getting lost in the rainforest.